2020
DOI: 10.1002/adma.202002936
|View full text |Cite
|
Sign up to set email alerts
|

A Moisture‐Hungry Copper Complex Harvesting Air Moisture for Potable Water and Autonomous Urban Agriculture

Abstract: The earth's atmosphere houses an enormous amount of water, which could be effectively exploited for a plethora of applications. While the development of materials for harnessing this abundant resource has gained impetus in recent years, limited efforts have been devoted to in‐depth research on their agricultural applications. Herein, a novel copper(II)–ethanolamine complex (Cu‐complex), which has a maximum water uptake of up to 300% and a water production rate of 2.24 g g−1 h−1 under natural sunlight, is repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 37 publications
1
105
0
Order By: Relevance
“…8 The working performance of SAWH system is strongly dependent on the water sorption capacity of sorbents; however, traditional porous sorbents (e.g., silica gels and zeolites) provide low water productivity because of their poor water sorption performance at low RH. 9 Therefore, many novel sorbents such as metal-organic frameworks (MOFs), [10][11][12][13][14] hydrogels, [15][16][17] liquid solutions, 18,19 and composite sorbents 20,21 with extraordinary performance were designed and exploited by the efforts from materials scientists in past years. Lately, these novel sorbents with high water sorption performance and special thermal/electrical effects also inspired energy-related applications such as energy storage, 22,23 thermal management, [24][25][26][27] electricity/fuel generations, 28,29 or co-application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The working performance of SAWH system is strongly dependent on the water sorption capacity of sorbents; however, traditional porous sorbents (e.g., silica gels and zeolites) provide low water productivity because of their poor water sorption performance at low RH. 9 Therefore, many novel sorbents such as metal-organic frameworks (MOFs), [10][11][12][13][14] hydrogels, [15][16][17] liquid solutions, 18,19 and composite sorbents 20,21 with extraordinary performance were designed and exploited by the efforts from materials scientists in past years. Lately, these novel sorbents with high water sorption performance and special thermal/electrical effects also inspired energy-related applications such as energy storage, 22,23 thermal management, [24][25][26][27] electricity/fuel generations, 28,29 or co-application.…”
Section: Introductionmentioning
confidence: 99%
“…The recently reported hydrogels not only present high-water capture capacity but also have many other desirable superiorities of thermo-response, 15,[38][39][40] fast sorption-desorption kinetics, 41 and low-cost, showing a promising application in the agricultural irrigation. 21,42 In comparison with above state-of-art sorbents, the hygroscopic sorbents of lithium chloride (LiCl), calcium chloride (CaCl 2 ), and ion solutions have strong competitiveness for SAWH at arid regions due to their higher water uptake at low RH. In our previous work, we elaborated the multi-step water sorption mechanism of hygroscopic salts that integrating the chemisorption, deliquescence, and solution absorption processes, obtaining a high-water uptake at low RH.…”
Section: Introductionmentioning
confidence: 99%
“…[ 102 ] Recently, Yang et al reported a complex of CuCl 2 and ethanolamine with excellent hygroscopicity. [ 21 ] Coupling with the photothermal agent such graphene, CNT, or carbon black, a photothermal humidification/dehumidification system was constructed for solar‐powered smart farms.…”
Section: Sustainable Applications Of Photothermal Materialsmentioning
confidence: 99%
“…[20] Combined with hygroscopic materials, the photothermal evaporator can capture moisture from the environment and produce clean water through a condensation-evaporation cycle. [21] Moreover, the latent heat, [22] temperature or salt concentration gradient, [10,23] as well as the water flow during evaporation, can drive an energy-generation process along with desalination, acquiring both freshwater and electricity simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Separating oil and water is currently a global challenge. [2][3][4][5][6][7][8][9][10][11][12][13][14] Thus, more effort is required for the construction of effective systems based on functional materials, devices, and techniques that facilitate the sustainable separation of oil/ water mixtures (O/W-Ms) to obtain clean water and to enable the recycling of expensive oil. Water is often "polluted" by oil and forms oil/water layered mixtures (O/W-LMs), oil-in-water emulsions (O/W-Es), and water-in-oil emulsions (W/O-Es).…”
mentioning
confidence: 99%